RELATIONSHIP BETWEEN METAL WATER CONCENTRATION AND ANTHROPOGENIC PRESSURES IN A TROPICAL WATERSHED, BRAZIL - Horn, Adolf Heinrich; Torres, Isabela Claret; Ribeiro, Elizene Velloso; Magalhães Junior, Antônio Perreira (Geochimica Brasiliensis, 2017)
In developing countries, Rivers are used to dispose wastewater from many human activities that may result in an input of metals to the water bodies. The São Francisco watershed is of extreme importance to Brazil as it drains large areas most of them with high hydric deficit. Besides being an important water resource to the local population several anthropogenic activities are developed in its watershed and compromise its water quality. The main objective was to address the relationship between metal concentration and anthropogenic pressures in São Francisco River. A Principal Component Analysis was used to determine a relationship between human activities and water metal concentration and to verify if there was a seasonal trend. Several metals in particulate and dissolved forms were measured in water from 59 points, collected during a “wet” and “dry” seasons, and analyzed using ICP-OES. The results showed that there was a clear correlation of particulate metal concentration with “wet” season, while the dissolved forms were highest in the “dry” season. The suspended particulate matter also showed clearly higher concentration during the “wet” season indicating important surface runoff input related to agricultural activities. Higher particulate metal concentration was found in areas with agricultural practices where the dissolved metals were the main forms in industrial sites. The results indicate that metals associated with soil particles enter the river with surface runoff. On the other side the treatment of industrial effluents are being successful in retaining metals in particulate but dispose metal in dissolved form in the river.